Vitamin D deficiency in Korean children: prevalence, risk factors, and the relationship with parathyroid hormone levels - Chung, In Hyuk (The Korean Society of Pediatric Endocrinology, 2014)
PURPOSE: This study was performed to investigate the relationship between serum vitamin D and parathyroid hormone (PTH) levels as well as to describe the prevalence and the risk factors of vitamin D deficiency (VDD) in Korean children. METHODS: Participants were 1,212 children aged 4 to 15 years, who visited Bundang CHA Medical Center (located at 37°N) between March 2012 and February 2013. Overweight was defined as body mass index≥85th percentile. Participants were divided into 4 age groups and 2 seasonal groups. VDD was defined by serum 25-hydroxyvitamin D (25OHD) <20 ng/mL. RESULTS: The level of 25OHD was significantly lower in overweight group than in normal weight group (17.1±5.1 ng/mL vs. 19.1±6.1 ng/mL, P<0.001). Winter-spring season (odds ratio [OR], 4.46; 95% confidence interval [CI], 3.45-5.77), older age group (OR, 1.60; 95% CI, 1.36-1.88), and overweight (OR, 2.21; 95% CI, 1.62-3.01) were independently related with VDD. The PTH levels were significantly higher in VDD group compared to vitamin D insufficiency and sufficiency group (P<0.001). In normal weight children, 25OHD (β=-0.007, P<0.001) and ionized calcium (β=-0.594, P=0.007) were independently related with PTH, however, these associations were not significant in overweight children. CONCLUSION: VDD is very common in Korean children and its prevalence increases in winter-spring season, in overweight children and in older age groups. Further investigation on the vitamin D and PTH metabolism according to adiposity is required.